Face localization for facial features extraction using a symmetrical filter and linear Hough transform - Arof, Hamzah (Springer, 2008)
In this paper, face localization for facial feature extraction is presented. The method consists of three steps: (1) facial features enhancement using symmetrical filter, and then the morphological process is applied to examine the edge, peaks, and valley fields; (2) line construction using linear Hough transform; (3) localization of the face region based on the constructed lines and the elimination of excess areas outside the face boundary. © 2008 International Symposium on Artificial Life and Robotics (ISAROB).